One-step mass-production of CeO2 nanoparticles embedded in free-standing porous carbon as haloperoxidase mimetic coating to combat biofouling on steel surface - Chao Zhao; Xinyu Wu; Tianqi Cheng; Tsz Yeung Yip; Bo Yuan; Wanqing Dai; Shengpei Zhang; Yuwei Qiu; Jian Lin Chen; Shang-Wei Chou; Yung-Kang Peng (Applied Surface Science Advances)
Marine biofouling poses significant challenges for maritime industries, leading to increased maintenance costs and ecological disturbances. While Cu-based biocide coatings are effective in combating biofouling, they raise environmental concerns and have limited lifespans. This has spurred interest in sustainable alternatives inspired by marine organisms, such as haloperoxidases (HPOs) found in certain algae, which can convert H2O2 and Br− in seawater into HOBr to mitigate biofouling. However, the practical implementation of HPOs is limited by their stability and cost. Nanozymes like CeO₂ have emerged as promising alternatives; however, conventional coating methods—typically involving the replacement of Cu-based biocides with CeO2 nanoparticles (NPs) in resin—restrict their exposure to H2O2 and Br⁻, resulting in significant activity loss. This study presents a simple method for mass-producing CeO2 NPs embedded in free-standing porous carbon as HPO mimetics. The optimized sample demonstrates exceptional HPO-like activity and antibacterial performance. Most importantly, we have shown that these HPO mimetics can be directly grown on steel surfaces during preparation, eliminating the need for a dispersant. This direct coating technique effectively addresses the challenges associated with conventional resin method, facilitating the development of a sustainable antibacterial and antifouling coating with preserved activity.